Resiliensi Kognitif dan Digital Wellbeing: Strategi Mitigasi Burnout Produktivitas di Era Kerja Hyper-Connected - Sukiman Makalalag; Cut Dinda Sara; Dedi Sulistiyo Soegoto (Jurnal Bisnis Inovatif dan Digital, 2026)
The hyper-connected work era has fundamentally blurred the temporal and psychological boundaries between professional and personal spheres, triggering a productivity paradox phenomenon where increased digital connectivity is inversely proportional to long-term cognitive efficiency. Consequently, this research aims to explore deeply and comprehensively the critical roles of cognitive resilience and digital wellbeing strategies as vital preventive mechanisms against the rising risk of burnout resulting from cumulative cognitive fatigue. Employing a qualitative approach with a rigorous literature review design, this study synthesizes extensive secondary literature retrieved from accredited academic databases and global policy reports within the last five years to analyze current trends and theoretical frameworks. The in-depth analysis reveals that cognitive resilience, significantly bolstered by metacognitive digital literacy, functions as an adaptive shield against the mounting pressures of information overload and attention fragmentation. Furthermore, the findings emphatically confirm that sustainable productivity is not achieved through borderless connectivity, but rather necessitates disciplined cognitive energy management and the strict implementation of "right to disconnect" protocols. Concluding the study, it is strongly recommended that organizations integrate comprehensive digital wellbeing policies into their work culture architecture to safeguard long-term employee performance and ensure organizational sustainability amidst the challenges of the attention economy.